Digital education for graduate students: literacy and skills development—A case study of non-linear control systems course - Huang, Zixin; Li, Ziqian; Wang, Lejun; Liu, Hao (Frontiers in Education, 2025)
The transformative integration of digital technologies into occupational frameworks and talent competency ecosystems has established educational digitalization and graduate digital literacy enhancement as pivotal components of national reform strategies, particularly within control science disciplines facing AI-driven industrial transformations. Addressing the critical demand for high-level research capabilities, this study employs a mixed-methods approach to investigate sustainable digital literacy cultivation pathways through a longitudinal case study (2020–2023) of the Non-linear Control Systems course. A pedagogical framework was developed, integrating three core mechanisms: goal-oriented instructional design aligned with DIGCOMP 2.2 standards and a quadruple mentorship system encompassing digital literacy, academic, project, and enterprise mentors. Implementation outcomes demonstrated statistically significant advancements, including a 55%−68% improvement in technical problem-solving competencies (p < 0.01). Student satisfaction rates surged from 78% to 95.45%, with medium-tier academic performances eliminated post-intervention. These findings substantiate the framework's efficacy in bridging theoretical-practical gaps through competency-based assessment protocols and adaptive mentorship architectures. The study contributes actionable strategies for engineering education reform, including scalable curriculum-digitization models and evidence-based industry-education integration frameworks, ultimately cultivating professionals equipped with sustainable digital competencies for intelligent manufacturing ecosystems.